Analyzing the greenhouse gas impact potential of smallholder development actions across a global food security program - Grewer, Uwe; Nash, Julie; Gurwick, Noel; Bockel, Louis; Galford, Gillian L.; Richards, Meryl B.; Costa, Ciniro; White, Julianna M.; Pirolli, Gillian; Wollenberg, Eva Karoline (IOP Publishing, 2018)
This article analyses the greenhouse gas (GHG) impact potential of improved management practices and technologies for smallholder agriculture promoted under a global food security development program. Under 'business-as-usual' development, global studies on the future of agriculture to 2050 project considerable increases in total food production and cultivated area. Conventional cropland intensification and conversion of natural vegetation typically result in increased GHG emissions and loss of carbon stocks. There is a strong need to understand the potential greenhouse gas impacts of agricultural development programs intended to achieve large-scale change, and to identify pathways of smallholder agricultural development that can achieve food security and agricultural production growth without drastic increases in GHG emissions.